Higher Mass Accuracy MALDI‐TOF/TOF Lipid Imaging of Human Brain Tissue in Alzheimer's Disease. Issue 1 (8th February 2019) - O'Rourke, Matthew B.; Smith, Caine C.; De La Monte, Suzanne M.; Sutherland, Greg T.; Padula, Matthew P.
Abstract: Matrix‐assisted laser desorption/ionization imaging mass spectrometry (MALDI‐IMS) is a well‐established technique for elucidating the location and relative abundance of a range of biomolecules. More recently, research into this technique has shifted from simple discovery and demonstration of utility to application in biomedical research. Here, we describe a protocol utilizing MALDI‐IMS for the spatial mapping of lipids in brain tissue from normal human brains and brains from patients with Alzheimer's disease, in the context of Alzheimer's disease. Improved accuracy calibration of the instrument from the tissue surface is emphasized, as this allows for significantly improved mass determination in time of flight (TOF)‐based instruments enabling more confident preliminary lipid identification. This improved initial result allows MALDI‐IMS data to be complemented with additional instrumentation, such as liquid chromatography mass spectrometry workflows or specialized non‐TOF systems such as Fourier transform cyclotron resonance instruments. This method is not limited to human tissue and can be applied to virtually any lipid‐rich formalin‐fixed tissue. © 2019 by John Wiley & Sons, Inc.